A comparative analysis of green financial policy output in OECD countries. (2nd July 2021) - Steffen, Bjarne
Abstract: The mitigation of dangerous climate change requires massive investments in low-carbon technologies. Accordingly, the redirection of finance flows is a key objective of the Paris Agreement, and countries have started to enact policies to influence financial actors to this end. However, transparency on such policies is low, and it is hardly possible to compare policy activity internationally. To fill this gap, here we present a comparative analysis of green financial policy output in OECD countries from 2001 to 2019, based on a newly compiled inventory of 136 policies from 29 countries and the European Union. We show that policy output accelerated rapidly since the Paris Agreement, with countries implementing 3.3 policies on average using various governing resources. Key instruments include carbon disclosure requirements, low-carbon investment policies for public funds, and green state investment banks. However, there are huge differences in policy output between countries, and some countries that host important financial centers have implemented few policies to date. On the basis of our results, we develop a research agenda to deepen the understanding of this important but little-studied area of climate policies.